Conceptualising and measuring mindfulness during worship and prayer: Scale development and initial validation of the Mindfulness during Worship Scale (MWS). (October 2022) - Yousaf, Omar; Love, Steven; Hampson, Peter; Hedderly, James; Rogers, Monica
Abstract: Objective: To propose a three-factor framework for conceptualising and measuring mindfulness during worship, and to develop and validate a new scale using existing scales of mindfulness and spirituality. Methods: A shortlist of scale items was developed and administered online to 521 Christians from the United Kingdom in three independent studies. Results: The studies confirmed a three-factor structure of the new 15-item Mindfulness during Worship Scale (MWS) with an overall internal reliability range of α = 0.81–0.87: a) concentration during worship, which contains reverse-scored items capturing the tendency for attention to slip towards unrelated activities during worship, b) presence during worship, which includes items relating to an increased awareness to thoughts and feelings as they relate to the engagement of worship, and c) absorption during worship, which includes items relating to an increased feeling of awareness and absorption in worship. Concurrent validity was confirmed, as the total MWS and subscale scores were positively associated with existing measures of mindfulness (FFMQ-15 and MAAS) and spirituality (ISS). Moreover, worship frequency predicted higher scores on all three MWS subscales, higher Scripture reading frequency predicted greater focus on religious thoughts during worship, and regular meditation practice was associated with a greater absorption during worship. The frequency of performing communal religious activities was not associated with mindfulness during worship. Conclusions: The MWS is the first scale that measures mindfulness specifically within the context of worship and prayer, and can be used within any religious community that engages in prayers. Highlights: Being mindful during the prayer can be measured. Worship and mindfulness are related in different ways. Individuals are different in how present they are during prayer. Spirituality is linked to being present during prayer.